Long‐term cannabidiol treatment for seizures in patients with tuberous sclerosis complex: An open‐label extension trial - Thiele, Elizabeth A.; Bebin, E. Martina; Filloux, Francis; Kwan, Patrick; Loftus, Rachael; Sahebkar, Farhad; Sparagana, Steven; Wheless, James (Epilepsia (Copenhagen), 2022)
Objective To evaluate the long‐term safety and efficacy of add‐on cannabidiol (CBD) in patients with seizures associated with tuberous sclerosis complex (TSC) in the open‐label extension (OLE) of the randomized, placebo‐controlled phase 3 trial GWPCARE6 (NCT02544763). Results of an interim (February 2019 data cut) analysis are reported. Methods Patients who completed the randomized trial enrolled to receive CBD (Epidiolex® in the United States; Epidyolex® in the EU; 100 mg/mL oral solution). The initial target dose was 25 mg/kg/day, which, based on response and tolerability, could be decreased or increased up to 50 mg/kg/day. The primary end point was safety. Key secondary end points included percentage reduction in TSC‐associated (countable focal and generalized) seizures, responder rates, and Subject/Caregiver Global Impression of Change (S/CGIC). Results Of 201 patients who completed the randomized phase, 199 (99%) entered the OLE. Mean age was 13 years (range, 1–57). At the time of analysis, 5% of patients had completed treatment, 20% had withdrawn, and 75% were ongoing. One‐year retention rate was 79%. Median treatment time was 267 days (range, 18–910) at a 27 mg/kg/day mean modal dose. Most patients (92%) had an adverse event (AE). Most common AEs were diarrhea (42%), seizure (22%), and decreased appetite (20%). AEs led to permanent discontinuation in 6% of patients. There was one death that was deemed treatment unrelated by the investigator. Elevated liver transaminases occurred in 17 patients (9%) patients; 12 were taking valproate. Median percentage reductions in seizure frequency (12‐week windows across 48 weeks) were 54%–68%. Seizure responder rates (≥50%, ≥75%, 100% reduction) were 53%–61%, 29%–45%, and 6%–11% across 12‐week windows for 48 weeks. Improvement on the S/CGIC scale was reported by 87% of patients/caregivers at 26 weeks. Significance In patients with TSC, long‐term add‐on CBD treatment was well tolerated and sustainably reduced seizures through 48 weeks, with most patients/caregivers reporting global improvement.